Fluorescent Microscopy-Based Detection of Chitin in Intact Drosophila melanogaster - Flaven-Pouchon, J.; Moussian, B. (Frontiers in Physiology, 2022)
Chitin is the major scaffolding component of the insect cuticle. Ultrastructural analyses revealed that chitin adopts a quasi-crystalline structure building sheets of parallel running microfibrils. These sheets called laminae are stacked either helicoidally or with a preferred orientation of the microfibrils. Precise control of chitin synthesis is mandatory to ensure the correct chitin assembly and in turn proper function of cuticular structures. Thus, evaluation of chitin-metabolism deficient phenotypes is a key to our understanding of the function of the proteins and enzymes involved in cuticle architecture and more generally in cuticle biology in insects. Usually, these phenotypes have been assessed using electron microscopy, which is time-consuming and labor intensive. This stresses the need for rapid and straightforward histological methods to visualize chitin at the whole tissue level. Here, we propose a simple method of chitin staining using the common polysaccharide marker Fluorescent brightener 28 (FB28) in whole-mount Drosophila melanogaster. To overcome the physical barrier of FB28 penetration into the cuticle, staining is performed at 65°C without affecting intactness. We quantify FB28 fluorescence in three functionally different cuticular structures namely wings, dorsal abdomens and forelegs by fluorescence microscopy. We find that, as expected, cuticle pigmentation may interfere with FB28 staining. Down-regulation of critical genes involved in chitin metabolism, including those coding for chitin synthase or chitinases, show that FB28 fluorescence reflects chitin content in these organs. We think that this simple method could be easily applied to a large variety of intact insects.